1977
DOI: 10.1093/infdis/136.supplement_3.s466
|View full text |Cite
|
Sign up to set email alerts
|

The Immunizing Effect of Influenza A/New Jersey/76 (Hsw1N1) Virus Vaccine Administered Intradermally and Intramuscularly to Adults

Abstract: 2The immunogenicity and reactogenicity of inactivated influenza A/New Jersey/76 (Hsw1N1) whole-virus vaccine administered intradermally (40 chick cell-agglutinating units/0.1-ml dose) and intramuscularly (im; 200 chick cell-agglutinating units/0.5-ml dose) to human adults were evaluated. Among 18-24-year-old persons initially free of detectable antibody, intradermal vaccination induced lower titers of hemagglutination-inhibiting antibodies than did im vaccination, and a sequence of intradermal and im vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The potential to spare dose by i.d. administration was suggested over 25 years ago (10,20,24) and has received renewed attention recently (8,29,31). However, the lack of a reproducible and easy-to-use i.d.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential to spare dose by i.d. administration was suggested over 25 years ago (10,20,24) and has received renewed attention recently (8,29,31). However, the lack of a reproducible and easy-to-use i.d.…”
Section: Discussionmentioning
confidence: 99%
“…delivery of a low dose (e.g., 0.1 ml) of influenza vaccine to i.m. or subcutaneous injection of a high dose (e.g., 0.5 ml), but did not conduct direct head-to- head comparisons of the two methods of delivery at the lower dosage level (6,8,10,20,24,29). Here, we conducted dose titration studies in animals in which i.m.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies clearly showed that intradermal vaccination with low-dose monovalent or bivalent influenza vaccines induced antibody titers comparable to or higher than those induced by the full-dose intramuscular vaccination. 117,118 Interestingly, however, the beneficial effect of the intradermal route was less evident in subjects aged over 50 y, suggesting a potential role of aging in diminishing the immune response triggered by intradermal vaccination. 118 More recently, a substantial number of clinical studies have evaluated intradermal administration of influenza vaccine to individuals of all ages, including the elderly.…”
Section: Novel Delivery Approachesmentioning
confidence: 99%